Fluctuations in airway bacterial communities associated with clinical states and disease stages in cystic fibrosis - Carmody, Lisa A. (PLoS One, 2018)
Bacteria that infect the airways of persons with cystic fibrosis (CF) include a group of well-described opportunistic pathogens as well as numerous, mainly obligate or facultative anaerobic species typically not reported by standard sputum culture. We sequenced the V3-V5 hypervariable region of the bacterial 16S rRNA gene in DNA derived from 631 sputum specimens collected from 111 CF patients over 10 years. We describe fluctuations in the relative abundances of typical CF pathogens, as well as anaerobic species, in relation to changes in patients’ clinical state and lung disease stage. Both bacterial community diversity and the relative abundance of anaerobes increased during exacerbation of symptoms (prior to antibiotic treatment), although this trend was not observed uniformly across disease stages. Community diversity and the relative abundance of anaerobic species decreased during antibiotic treatment. These results support current hypotheses regarding the role of anaerobes in CF pulmonary exacerbations and lung disease progression.